Legal Protection for Children in Conflict with the Law Under the Law on the Juvenile Criminal Justice System in Indonesia - Elizabeth Ghozali; Muhammad Ansori Lubis (CV. RADJA PUBLIKA, 2025)
This research is entitled Legal Protection for Children in Conflict with the Law in a Review According to the Law on the Juvenile Criminal Justice System in Indonesia. The method used in this paper is based on normative juridical research. Writing in this scientific journal uses a statutory and conceptual approach. Journals that use normative legal research are by collecting secondary data sources in the field of law from the point of view of their binding strength. In the normative research method, various library materials are used in accordance with the legal issues being studied. The Law on the Juvenile Criminal Justice System provides a new color in the dynamics and development of law in Indonesia, especially towards the criminal law system. From experience in handling the problem of children in conflict with the law, when all parties play an active role, especially the government, then the number of juvenile delinquents which is now increasing can be suppressed and handled properly. In terms of giving special attention to children's problems, the government must seriously and fully implement what has been mandated by law. There is a need for a national comprehensive child protection system to prevent and deal with violence or exploitation of children in conflict with the law. Thus, the protection of children is not only limited to the government as administrators of the state, but also carried out by parents, families and communities to be responsible for protecting and maintaining children's human rights. On the other hand.